Development of stabilized tenofovir disoproxil tablet: degradation profile, stabilization, and bioequivalence in beagle dogs - Oh, Ga Hui; Kim, Joo Eun; Park, Young Joon (Drug Development and Industrial Pharmacy, 2018)
The purpose of this study was to develop a hydrolysis-resistant optimized oral formulation of tenofovir disoproxil (TD) using a stabilizer. To develop a stabilized TD tablet bioequivalent to the commercial TD fumarate (TDF, Viread®) tablet, TD free base was prepared and its degradation profile and stability were investigated. The TD tablet showed antiviral activity, but its absorption was limited in the intestinal tract because of premature degradation. The drug subjected to severe conditions for the stress test was catalyzed under neutral, basic, oxidative, and thermolytic conditions, whereas it was comparatively stable under acidic, photolytic, and humid states. The compatibility study showed that sodium bisulfite (SB) stabilized TD by preventing its degradation in aqueous and 3% peroxide solutions compared with the unstabilized TD. According to the stability analysis and degradation profile, four TD tablet formulations were prepared. The selected TD tablets were composed of non-hygroscopic excipients (lipophilic-fumed silica, anhydrous lactose, and microcrystalline cellulose [MCC]), SB, croscarmellose sodium (CCS), and hydrogenated castor oil (HCO), and were manufactured using a dry granulation method because of their hydrolytic properties. The stabilized TD tablet showed similar dissolution properties as the TDF (Viread®) reference tablet in pH 1.2, 4.0, and 6.8 and water. Moreover, the lower degradation rate of the tablet in simulated gastrointestinal fluid demonstrated that its intestinal absorption might have improved owing to prevention of its enzymatic hydrolysis and the pH effect. Finally, the formulated TD tablet was bioequivalent to the TDF (Viread®) reference tablet in beagle dogs.
Keywords: Animals; Carboxymethylcellulose Sodium; Dogs; Excipients; Lactose; Tablets; Tenofovir; Therapeutic Equivalency; bioavailability; bioequivalence; degradation profile; stabilization; Tenofovir disoproxil